Research Progress of Chinese Medicine in the Treatment of Lumbar Intervertebral Disc Herniation - Gan, Wenhui (International Journal of Public Health and Medical Research, 2025)
Lumbar intervertebral disc herniation is a common disease in orthopedics, which seriously affects the quality of life of patients. This paper summarizes the therapeutic principles and clinical applications of these three therapies by comprehensively analyzing the literature related to acupuncture, moxibustion and tuina in Chinese medicine in recent years, with the aim of providing clinicians with new therapeutic perspectives and optimizing the existing treatment protocols, with a view to providing patients with more efficient and high-quality treatments.